Additive manufacturing of a novel Ti-Al-V-Fe alloy using selective laser melting - Azizi, Hamid; Zurob, Hatem; Bose, Bipasha; Reza Ghiaasiaan, S.; Wang, Xiang; Coulson, Simon; Duz, Vlad; Phillion, A.B. (My University, 2018)
Ti-1Al-8V-5Fe (Ti-185) and other Fe containing β-Ti alloys are attractive because of their high strength and low cost. These alloys, however, cannot be produced through ingot casting due to strong Fe segregation and the formation of β flecks. Selective Laser Melting (SLM) was successfully used to produce Ti-185 components starting from elemental Ti and Fe powders, and an Al-V master alloy powder with irregular shape. Microstructure analysis of the as-built components demonstrated that SLM can be used to produce a very fine grain microstructure with nano-scale precipitates and non-detrimental Fe segregation. The findings are interpreted in terms of the rapid solidification conditions during SLM. Compression test results reveal that ultra-high strength and reasonable ductility can be achieved in the as-built as well as heat treated samples.
Keywords: Rapid solidification; Selective Laser Melting; Powder processing; Titanium alloys; Solidification microstructure